Shelf life enhancement of guava (Psidium guajava cv. Baruipur) stored under pilot scale modified atmosphere storage system. (October 2021) - Mangaraj, S; Thakur, Rajeev Ranjan; Mathangi, Raja Sekhar; Yadav, Ajay; Swain, Sachidananda
Modified atmosphere storage (MAS) structure of 100 kg capacity has been developed for prolonging the shelf life of fresh guava. The influence of MAS on guava was investigated at 10 and 25 °C of storage temperature with unpacked guava as control. During storage study, the quality parameters of MAS stored guava, namely physiological weight loss (PWL), firmness, color (L*, a*, b*) and total soluble solids (TSS) were found to be 5.49%, 143.78 N, 76.20, 5.58, 50.81 and 12.3 ˚brix respectively, after 9 days of storage at 25 °C and were very close to that of fresh guava. The quality analysis revealed that at 10 and 25 °C, guava can be stored up to 20 and 9 days respectively under MAS as compared to control sample having 7 and 4 days at 10 and 25 °C, respectively. Therefore, the developed MAS system can be widely used for handling, transportation and retailing of guava. Practical application: The developed modified atmosphere storage (MAS) system has increased the shelf life of Guava up to 20 and 9 days at 10 °C and 25 °C, respectively. This extended period will be very much effective for providing the buffer period to the fresh Guava and facilitate extra time to the farmers for its marketing. The uniquely developed MAS system is helpful for the farmers for on-farm storage of fresh Guava at a large scale and will provide smooth handling and transportation for retailing and marketing.